Why Inclusive Education? - Dimofte, Gherghina-Gina (Didactica Danubiensis, 2024)
The paper addresses the subject of inclusive education with a focus on the challenges and opportunities that arise in the modern school of the digital age. Inclusive education represents an educational system that promotes the participation and learning of all students regardless of their individual differences, abilities, needs, or characteristics. Its aim is to provide equal opportunities for all students by promoting diversity, respect, and acceptance. In an inclusive educational environment, all students are integrated into the same school community and receive the necessary support and resources to reach their maximum potential. The fundamental principles of inclusive education target aspects such as: promoting equal opportunities through equal access to educational opportunities for all students regardless of abilities, ethnic origin, socio-economic status, or other individual characteristics; respect for diversity by recognizing and celebrating diversity among students, creating an environment where everyone feels accepted and valued; developing social skills through interaction and collaboration among students, contributing to the development of social skills, empathy, and mutual understanding; developing a positive mindset by promoting an open attitude towards diversity and overcoming prejudices and stereotypes; preparing for life in a diverse world by helping them become active, empathetic, and understanding citizens. The benefits of inclusive education include improving school performance by adapting teaching and assessment methods to respond to the individual needs of students, which can enhance school performance and maximize each student's potential; reducing stigmatization and discrimination by highlighting that an inclusive educational environment promotes tolerance and acceptance, contributing to the reduction of stigmatization and discrimination. Additionally, it can build more inclusive societies because the impact of inclusive education extends beyond the school environment, contributing to the creation of a more inclusive and equitable society. Differentiating the curriculum by adapting the content, process, and product of learning to meet the individual needs of each student makes the school a stimulating environment conducive to the individual development of students according to their potential. The use of technology to facilitate communication and collaboration, the adaptation of educational materials and assessments, as well as the monitoring of student progress, emerges as a necessity but also as support in conducting a quality inclusive educational process. The implementation of inclusive education faces numerous challenges, including limited resources, the need for teacher training, as well as existing negative attitudes and mindsets, in addition to educational policies considered inadequate. In this context, technology brings both considerable opportunities and specific challenges. Therefore, technology can play a crucial role in supporting inclusive education, but it is essential to manage it properly to maximize benefits and minimize associated risks. Thus, inclusive education can become more accessible and effective for all students regardless of their specific needs.